A multiplex PCR assay to differentiate between dog and red fox - Weissenberger, Melanie; Reichert, Walter; Mattern, Rainer (Forensic science international. Genetics, 2011)
Foxes are frequently the cause of car accidents in Baden-Württemberg (BW, Germany). The domestic dog (Canis familiaris) is in close relation to the red fox (Vulpes vulpes) and the silver fox which is a coat colour variant of the red fox. As insurance claims that involve accidents with animals require authentication, we analyzed frequency distribution and allele sizes in two canine microsatellite loci in 26 dogs (different breeds) and 19 red foxes of the region of BW, Germany. Moreover, sequencing analysis was performed. Red foxes exhibited only 1 allele at each microsatellite locus, whereas in dog 7 alleles at the CPH4 locus and 6 alleles at the CPH12 locus were detected. Sequences of PCR products from the two species revealed several differences between dogs and foxes. We established a sequenced allelic ladder and give population data from dogs and red foxes from the region of BW, Germany. Using microsatellite polymorphisms is efficient in differentiating between dogs and foxes in forensic casework.